EVALUATION OF INTRAOPERATIVE NEUROPHYSIOLOGICAL MONITORING TECHNIQUES FOR PRESERVING NEURAL FUNCTION DURING COMPLEX NEUROSURGICAL PROCEDURES - Dr. Aditya Ashok; Dr. Shubhlesh Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Introduction: Intraoperative neurophysiological monitoring (IONM) emerged as a crucial tool for preserving neural function during complex neurosurgical procedures. This study aimed to comprehensively evaluate the effectiveness of various IONM techniques in detecting potential neural injury, guiding surgical decision-making, and assessing their impact on postoperative neurological outcomes, patient recovery, and quality of life.Methods: This prospective cross-sectional study was conducted at a tertiary care neurosurgical center. A sample of 126 participants aged 18 years or older, undergoing complex neurosurgical procedures involving manipulation near critical neural structures, were enrolled. IONM techniques, including electroencephalography (EEG), somatosensory evoked potentials (SSEPs), motor evoked potentials (MEPs), brainstem auditory evoked potentials (BAEPs), and direct nerve monitoring, were employed. Preoperative and postoperative neurological examinations, as well as patient-reported outcome measures (PROMs), were collected.Results: Electroencephalography (EEG) was employed in all cases, while SSEPs (85.7%), MEPs (76.2%), BAEPs (33.3%), and direct nerve monitoring (50.8%) were selectively utilized. The majority of participants (81.0%) experienced no neurological deficits postoperatively. IONM findings strongly correlated with postoperative neurological outcomes, with persistent abnormalities associated with a higher incidence of permanent deficits (1.6%). Significant improvements were observed in patient-reported quality of life, functional status, and pain levels postoperatively.Conclusion: The comprehensive evaluation of IONM techniques demonstrated their efficacy in detecting potential neural injury, guiding surgical decision-making, and contributing to improved postoperative neurological outcomes and patient-reported outcomes. Implementing standardized protocols, regular training, and ongoing research to enhance IONM practices were recommended.